The a to Z of Australian and New Zealand Cinema - Moran, Albert; Vieth, Errol (Rowman & Littlefield Publishers, 2009)
Whether it was Jane Campion's The Piano, Mel Gibson in Mad Max, Paul Hogan in Crocodile Dundee, or The Lord of the Rings saga, we have all experienced the cinema of Australia and New Zealand. This book is an introduction and guide to the film of Australia and New Zealand. With entries on many exceptional producers, directors, writers and actors, as well as the films indicated above and many others, this reference also presents the early pioneers, the film companies and government bodies, and much more in its hundreds of cross-referenced dictionary entries. Through a chronology that shows how far these cinemas have come in a short time and an introduction that presents them more broadly, a clear portrait of the two countries' motion pictures emerge. The bibliography is an excellent source for further reading.